ISLAMIC BROADCASTING DA'WAH THROUGH NEW MEDIA TRENDSETTERS (A STUDY OF OKI SETIANA DEWI'S DA'WAH ON YOUTUBE FROM THE PERSPECTIVE OF MEANINGS AND MEDIA): Dakwah Penyiaran Islam Melalui Trendsetter Media Baru (Studi Analisis Dakwah Oki Setiana Dewi di Youtube Perspektif Meanings and Media) - Isman Iskandar (Jurnal Diskursus Islam, 2025)
Abstract YouTube is a popular application that is connected to the internet to make a limited world infinite. However, the progress of digital media has had positive and negative impacts on users and those who control current trends, especially preachers who have to adapt from conventional media to digital media. This research aims to explore further how Oki Setiana Dewi preached YouTube as a trendsetter in today's new media. This research uses Branston and Stafford's theories on the meanings and media and Andi Faizal Bakti's concept of trendsetter communication in the digital era. The use of the concepts and theories above is able to analyze and discuss the problems in this research. The research method used is qualitative with analysis of Oki Setiana Dewi's YouTube content. The data collection methods used were interviews, observation, and documentation. The primary data used is a popular video entitled "Maryam's Way of Memorizing the Qur'an, Murajaah Everywhere" which has been watched 5 million times. The results of this research show that Oki Setiana Dewi as a communicator can use YouTube as a trendsetter media effectively. Oki Setiana Dewi uses the internet as a medium for da'wah where the Islamic messages conveyed can be understood in terms of denotation and connotation. The religious culture that is currently trending in the Indonesian Muslim community is competing to teach their children to memorize the Koran. The meaning of something that connects to culture as well as personal experience (denotation) makes Oki Setiana Dewi appear in cyberspace as an interesting figure who spreads noble values, ethics, and morals (akhlak).